2017
DOI: 10.1159/000468935
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and Frozen-Thawed Embryo Transfer Compared to Natural Conception: Differences in Perinatal Outcome

Abstract: Background/Aim: To compare the pregnancy outcome of singletons conceived after transfer of cryopreserved and thawed embryos (frozen embryo transfer [FET]) to singletons conceived after fresh embryo transfer (fresh ET) and natural conceived singletons. Methods: Using a retrospective data analysis on a study population consisting of 1,261 singletons born after FET and 2,519 singletons born after fresh ET between 2006 and 2015. The control group consisted of singletons born after natural conception. Main outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…Ten studies reported macrosomia outcomes in a total of 108.715 FET singletons. The risk of macrosomia in relation to FET was assessed in eight studies, of which six studies were included in meta‐analysis (Litzky et al, ; Maheshwari et al, ; Pinborg et al, ; Sazonova et al, ; Spijkers et al, ; Wennerholm et al, ). All of the studies included in meta‐analysis were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies reported macrosomia outcomes in a total of 108.715 FET singletons. The risk of macrosomia in relation to FET was assessed in eight studies, of which six studies were included in meta‐analysis (Litzky et al, ; Maheshwari et al, ; Pinborg et al, ; Sazonova et al, ; Spijkers et al, ; Wennerholm et al, ). All of the studies included in meta‐analysis were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…This should be considered when analyzing the increased risk of LGA in FET babies, as they normally have a higher birth order than children conceived after fresh embryo transfer. Yet, the difference in risk of LGA and macrosomia has persisted after adjustment for parity in several of the included studies (Li et al, ; Luke et al, ; Maheshwari et al, ; Marino et al, ; Pelkonen et al, ; Pinborg et al, ; Sazonova et al, ; Spijkers et al, ; Wennerholm et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spijker et al also showed the risk of high birth weight (>4,500g) and being large for gestational age was higher in the FTET group than in the FET group. 17 However, there were some studies reporting no difference of live birth weight between fetuses after FTET and FET. 18,19 Some results of studies related to the perinatal/obstetric outcome may be inconsistent, and they are mainly observational studies, thus it is considered that more randomized controlled studies are needed in the future.…”
Section: 5mentioning
confidence: 99%